A Versatile Theranostic Platform for Colorectal Cancer Peritoneal Metastases: Real‐Time Tumor‐Tracking and Photothermal‐Enhanced Chemotherapy. Issue 20 (16th August 2021) - Sun, Tao; Zhang, Guangping; Ning, Tingting; Chen, Qinjun; Chu, Yongchao; Luo, Yifan; You, Haoyu; Su, Boyu; Li, Chao; Guo, Qin; Jiang, Chen
Abstract: A versatile tumor‐targeting stimuli‐responsive theranostic platform for peritoneal metastases of colorectal cancer is proposed in this work for tumor tracking and photothermal‐enhanced chemotherapy. A quenched photosensitizer ("off" state) is developed and escorted into a tumor‐targeting oxaliplatin‐embedded micelle. Once reaching the tumor cell, the micelle is clasped to release free oxaliplatin, as well as the "off" photosensitizer, which is further activated ("turned‐on") in the tumor reducing microenvironment to provide optical imaging and photothermal effect. The combined results from hyperthermia‐enhanced chemotherapy, deep penetration, perfused O2, and the leveraged GSH‐ROS imbalance in tumor cells are achieved for improved antitumor efficacy and reduced systematic toxicity. Abstract : A versatile theranostic platform is developed for colorectal cancer peritoneal metastases, to realize real‐time tumor‐tracking and meanwhile photothermal‐enhanced chemotherapy.